2012
DOI: 10.1007/s10995-012-1050-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Child Care Providers Breastfeeding Support with Breastfeeding Duration at 6 Months

Abstract: Many lactating mothers participate in the workforce and have their infants cared for outside of their home, yet little is known about their child care providers' (CCPs') support of breastfeeding. This study examines the association between CCPs' breastfeeding support as reported by mothers at 3 months and mother's breastfeeding at 6 months. Infant Feeding Practices Study II, a longitudinal study, followed mothers of infants via mail questionnaires almost monthly from late pregnancy throughout the first year. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Our findings were consistent with other studies outcomes in the literature [27, 28, 30]. Batan et al [27] also found that good support from childcare providers at three months may help mothers to prolong breastfeeding up to six months.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings were consistent with other studies outcomes in the literature [27, 28, 30]. Batan et al [27] also found that good support from childcare providers at three months may help mothers to prolong breastfeeding up to six months.…”
Section: Discussionsupporting
confidence: 93%
“…Batan et al [27] also found that good support from childcare providers at three months may help mothers to prolong breastfeeding up to six months. This finding indicates the important role that can be played by childcare workers to enhance breastfeeding practice in the local population, as most of the babies were sent to them at the age of three months old, when most mothers return to work after their maternity leave is over.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and how to use this knowledge to best support mothers in achieving their breastfeeding goals (e.g. ).…”
mentioning
confidence: 99%
“…The longitudinal Infant Feeding Practices Study II surveyed mothers who had breastfed and used childcare about five potential breastfeeding supports from childcare providers. 13 Mothers who reported receiving all five supports were thrice as likely to be breastfeeding at 6 months, compared to mothers who felt they received fewer than three of these supports. In another study, an exploration into the association between childcare use, WIC participation, and breastfeeding duration found childcare use to be an independent risk factor for short breastfeeding duration.…”
Section: Introductionmentioning
confidence: 97%